2014
DOI: 10.1111/1758-2229.12161
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and plant‐dependent variations in diversity, abundance and stress tolerance of epiphytic yeasts in desert habitats

Abstract: We studied the epiphytic yeast species of the plants of the Negev Desert and the Dead Sea region, Israel, which are considered one of the most extreme hyper-arid lands in the world. For this purpose, we developed isolation protocols; we performed morphological, cultural and molecular identification tests and compared yeast diversity between the locations and the plants. The composition of the yeast populations present in the study's plants underwent seasonal fluctuations, whereas differences in community compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Filobasidium magnum was also detected in our study at a higher abundance and frequency ( Table S2 ). Filobasidium magnum , which has been reported from Arctic glaciers [ 34 , 63 ] and plants inhabiting the Negev Desert and the Dead Sea region [ 64 ], was observed in our sampling sites in the Qaidam Basin that is characterized by hyper-arid, alkaline, and hypersaline environments. Similarly, strains of F. magnum were also plant-related with frequent isolation from plants in our study, implying this species may help plants to survive in dry areas.…”
Section: Discussionmentioning
confidence: 66%
“…Filobasidium magnum was also detected in our study at a higher abundance and frequency ( Table S2 ). Filobasidium magnum , which has been reported from Arctic glaciers [ 34 , 63 ] and plants inhabiting the Negev Desert and the Dead Sea region [ 64 ], was observed in our sampling sites in the Qaidam Basin that is characterized by hyper-arid, alkaline, and hypersaline environments. Similarly, strains of F. magnum were also plant-related with frequent isolation from plants in our study, implying this species may help plants to survive in dry areas.…”
Section: Discussionmentioning
confidence: 66%
“…Further explanation of the co-occurrence of Mrakia and Glaciozyma -related taxon will be possible once the metabolic and other characteristics of the latter have been characterised further. Filobasidium species are widely spread, from very arid environments 99 to Italian glacial meltwaters 100 and basal ice of the High Arctic 4 . Species of the genus Naganishia are among the most resistant organisms to UV radiation 101 : they are found in many extreme environments such as high elevation soil of the Atacama Desert 101,102 , of the Antarctic Dry Valleys 81 , and of subglacial ice in Svalbard 4 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that A. melanogenium P5 strain isolated from the mangrove ecosystem was more thermotolerant than the yeast strain XJ5-1. In contrast, the epiphytic yeast strains isolated from the plants of the Negev Desert and the Dead Sea region, Israel, showed an unusual tolerance to extreme growth conditions, such as high temperatures (up to 72 % viability at 50 °C), lethal hydrogen peroxide and NaCl concentrations (Abu-Ghosh et al 2014). …”
Section: Response To Heat Treatmentmentioning
confidence: 98%